Jasmonic acid‐isoleucine formation in grapevine (Vitis vinifera L.) by two enzymes with distinct transcription profiles. Issue 7 (12th February 2015) - Böttcher, Christine; Burbidge, Crista A.; di Rienzo, Valentina; Boss, Paul K.; Davies, Christopher
Abstract The plant hormone jasmonic acid (JA) is essential for stress responses and the formation of reproductive organs, but its role in fruit development and ripening is unclear. Conjugation of JA to isoleucine is a crucial step in the JA signaling pathway since only JA‐Ile is recognized by the jasmonate receptor. The conjugation reaction is catalyzed by JA‐amido synthetases, belonging to the family of Gretchen Hagen3 (GH3) proteins. Here, in vitro studies of two grapevine (Vitis vinifera L. cv Shiraz) GH3 enzymes, VvGH3‐7 and VvGH3‐9, demonstrated JA‐conjugating activities with an overlapping range of amino acid substrates, including isoleucine. Expression studies of the corresponding genes in grape berries combined with JA and JA‐Ile measurements suggested a primary role for JA signaling in fruit set and cell division and did not support an involvement of JA in the ripening process. In response to methyl JA (MeJA) treatment, and in wounded and unwounded (distal) leaves, VvGH3‐9 transcripts accumulated, indicating a participation in the JA response. In contrast, VvGH3‐7 was unresponsive to MeJA and local wounding, demonstrating a differential transcriptional regulation of VvGH3‐7 and VvGH3‐9. The transient induction of VvGH3‐7 in unwounded, distal leaves was suggestive of the involvement of an unknown mobile wound signal.